POR QUE AS CIDADES SÃO VULNERÁVEIS? (Why the cities are vulnerable?) - Almeida, Lutiane Queiroz de (Revista da Casa da Geografia de Sobral (RCGS), 2012)
A pergunta que intitula o presente artigo se apresenta muito mais como uma provocação do que como a pretensão de explicar a grande diversidade de vulnerabilidades presentes nas cidades, mas pretende tangenciar aspectos ligados à diferenciação espacial das vulnerabilidades na cidade, ou seja, explicar por que determinados espaços e grupos sociais se apresentam com maior susceptibilidade a perigos naturais. Pretende-se também exemplificar o problema teórico-conceitual posto através de um estudo de caso sobre as vulnerabilidades sociais aos riscos naturais na Região Metropolitana de Fortaleza. No bojo do que se tem chamado de crise ambiental (na verdade a crise ambiental é uma crise da humanidade, e não da Natureza), há uma gama de outras questões também vinculadas à cidade, mas que refletem a conjuntura imposta pelo capitalismo de mercado, de competitividade, caso da pobreza e desigualdades socioespaciais, violência, entre outros. Toda essa ebulição social, cultural, econômica, tecnológica e espacial, também tem gerado uma série de ansiedades, medos, inseguranças. Aliás, Ulrich Beck tem denominado a sociedade pós-moderna de a “sociedade do risco”, dada a generalização de riscos diversos, perigos, vulnerabilidades, exposições, incertezas, inseguranças e medos, que são elementos típicos da sociedade atual, que é também urbana, complexa e caracterizada pelas múltiplas espacialidades. Palavras-chave: Cidades. Sociedade do Risco. Vulnerabilidade. WHY THE CITIES ARE VULNERABLE? Abstract The question that entitles the present article is a provocation. The article intends to approach on aspects to the space differentiation of the vulnerabilities in the city, that is, to explain why some spaces and social groups present with bigger exposure to the atural hazards. Another aim is to illustrate the theoretical and conceptual problem put through a case study on social vulnerability to natural hazards in the Metropolitan Area of Fortaleza. The humanity has passed in last the 50 years for intense changes in its social, economic, cultural and environmental structure. Such changes in the last few decades have one strong entailing with the intense evolution in the scientific and technological field, what it has excited an influence in such way, that made with that some researchers called this historical moment After-Modernity. In the bulge of what it has been called environmental crisis (in the truth the environmental crisis is a crisis of the humanity, and not of the Nature), has a gamma of other questions also tied with the city, but that they reflect the conjuncture imposed for the market capitalism, of competitiveness, case of the poverty and space inequalities, violence, among others. All this social, cultural, economic, technological and space boiling, also has generated a series of anxieties, fears, unreliabilities. By the way, Ulrich Beck has called the society after-modern of the “risk society”, given to the generalization of diverse risks, hazards, vulnerabilities, exposures, uncertainties, unreliabilities and fears, that are typical elements of the current society that is also urban, complex and characterized for the multiple spaciabilities. Keywords: Cities. Risk society. Vulnerability.